Is That a Gun in Your Pocket? Dilemmas of Student and Academic Services Professionals in a Campus Carry State - Somers, Patricia; Fry, Jessica J; Jones, Ashley; Newton, AJ (The College student affairs journal, 2020)
Concealed campus carry is the subject of both popular discussion and academic scholarship. For almost a decade, the University of Texas at Austin (UT) has been the site of the debate over campus carry during a prolonged legislative battle and an implementation marked by pro- and anti-gun protests, various Texas attorney general's opinions, and lawsuits. Using selfdetermination theory (Deci & Ryan, 2000), this article presents the results from in-depth interviews with 32 women professionals in academic and student services at UT about how campus carry affects their personal and professional lives. Because of their daily interactions with students, these professionals have been at the forefront of implementing state and campus gun policies. Their experiences can inform the development of campus carry law, policy, and implementation at other universities.